2011
DOI: 10.1210/en.2011-0287
|View full text |Cite
|
Sign up to set email alerts
|

Specific Regulatory Motifs Predict Glucocorticoid Responsiveness of Hippocampal Gene Expression

Abstract: The glucocorticoid receptor (GR) is an ubiquitously expressed ligand-activated transcription factor that mediates effects of cortisol in relation to adaptation to stress. In the brain, GR affects the hippocampus to modulate memory processes through direct binding to glucocorticoid response elements (GREs) in the DNA. However, its effects are to a high degree cell specific, and its target genes in different cell types as well as the mechanisms conferring this specificity are largely unknown. To gain insight in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 32 publications
2
50
1
1
Order By: Relevance
“…Possibly, the presence of particular GR cofactors are responsible for a cell-type specific response to GR activation (e.g., Grenier et al, 2006;see also below). Contrary to the previously described effect of GCs on other brain regions such as the hippocampus (Datson et al, 2011) or hypothalamus (Verkuyl et al, 2004;Sato et al, 2008), there are no data to date demonstrating the transcriptional effect of GR stimulation in striatal neurons. It has been reported that dexamethasone administration dose-dependently induces the death of selective subtypes of striatal neurons (enkephalin-positive neurons), as well as hippocampal and septal neurons (Haynes et al, 2001).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigcontrasting
confidence: 80%
“…Possibly, the presence of particular GR cofactors are responsible for a cell-type specific response to GR activation (e.g., Grenier et al, 2006;see also below). Contrary to the previously described effect of GCs on other brain regions such as the hippocampus (Datson et al, 2011) or hypothalamus (Verkuyl et al, 2004;Sato et al, 2008), there are no data to date demonstrating the transcriptional effect of GR stimulation in striatal neurons. It has been reported that dexamethasone administration dose-dependently induces the death of selective subtypes of striatal neurons (enkephalin-positive neurons), as well as hippocampal and septal neurons (Haynes et al, 2001).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigcontrasting
confidence: 80%
“…The presently modest predictive power may be improved by incorporating the effect size (i.e., the absolute expression of a gene), given the values for true positives Irs4 and Magel2. Also, the presence of conserved steroid response elements on the DNA could be a useful additional filter (38).…”
Section: Discussionmentioning
confidence: 99%
“…6E). Less is known about the expression of these genes in the peripheral tissues we examined, but binding of GR to GR-elements is highly tissue-specific (23), and although our data do not conclusively demonstrate that GR actively regulates Suv39h2 expression in the hippocampus, they do suggest that the changes in H3K9 methylation we have observed in the hippocampus may use a different mechanism than has been observed elsewhere in the brain (e.g., the accumbens, where G9a appears to be the dominant H3K9 methyltransferase) (24). It should also be added that our examination of stress-responsive brain regions and tissues was not comprehensive, so it is possible that other stress-responsive regions, such as the amygdala or paraventricular hypothalamus, could show similar changes in H3K9 methylation or transposon expression as a consequence of stress.…”
Section: Discussionmentioning
confidence: 99%